Bridging the gap: Project based-writing procedure texts as a pathway to real-world jobs for vocational students - Sutisna Yanto, Elih; Firdaus, Irma Maulia; Nugraha, Sidik Indra (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2023)
This best practice article presents a guided teaching strategy aimed at vocational students to improve their procedure text writing skills. The practical application-focused program focuses on developing students' understanding, writing skills, and speaking in professional contexts. The challenges vocational students face in combining technical expertise with clear communication are addressed through interactive activities, self-correction techniques, and various presentation methods. Systemic Functional Linguistics (SFL) genre pedagogy and the Teaching and Learning Cycle (TLC) form the basis of the teaching approach. The study, conducted in a West Java vocational school, uses a case study design that demonstrates the coexistence of anxiety and excitement, the effectiveness of collaboration, and strategies for overcoming obstacles in learning procedure texts. The findings highlight the central role of teaching strategy in preparing vocational students to communicate effectively in their professional activities.